Respuesta :
Answer:
c. subtract 7 from both sides and then divide both sides by -2
Explanation:
Step 1 - Subtract 7 from both sides
-2b + 7 = -13
-2b + 7 - 7 = -13 - 7
-2b = -20
Step 2 - Divide both sides by -2
-2b = -20
-2b / -2b = -20 / -2b
b = 10
c. subtract 7 from both sides and then divide both sides by -2
Explanation:
Step 1 - Subtract 7 from both sides
-2b + 7 = -13
-2b + 7 - 7 = -13 - 7
-2b = -20
Step 2 - Divide both sides by -2
-2b = -20
-2b / -2b = -20 / -2b
b = 10
Answer:
Subtract 7 from each side
Divide each side by -2
Step-by-step explanation:
-2b+7 = -13
Subtract 7 from each side
-2b+7 -7= -13-7
-2b = -20
Divide each side by -2
-2b/-2 = -20/-2
b = 1-